Gravity Field of Ganymede After the Juno Extended Mission. Issue 24 (14th December 2022) - Gomez Casajus, L.; Ermakov, A. I.; Zannoni, M.; Keane, J. T.; Stevenson, D.; Buccino, D. R.; Durante, D.; Parisi, M.; Park, R. S.; Tortora, P.; Bolton, S. J.
Abstract: The Juno Extended Mission presented the first opportunity to acquire gravity measurements of Ganymede since the end of the Galileo mission. These new Juno data offered the chance to carry out a joint analysis with the Galileo data set, improving our knowledge of Ganymede's gravity field and shedding new light upon its interior structure. Through reconstruction of Juno 's and Galileo 's orbit during the Ganymede flybys, the gravity field of the moon was estimated. The results indicate that Ganymede's degree‐2 field is compatible with a body in hydrostatic equilibrium within 1− 𝜎 and hint at regional gravity anomalies with amplitudes exceeding those inferred by Cassini for Titan. Our explicit treatment of non‐hydrostatic effects leads to wider confidence intervals for the derived moment of inertia with respect previous analyses. The higher central value of the derived moment of inertia indicates a lesser degree of Ganymede's differentiation. Plain Language Summary: On 7 June 2021, Juno performed the first close flyby of Ganymede, the largest satellite of Jupiter (and the largest moon in the Solar System), since the end of the Galileo mission. The gravity field of Ganymede was reconstructed using the radio tracking data from all of the Ganymede encounters of both the Galileo and Juno missions. The data analysis hints at localized gravity anomalies. Interpretation of the gravity data suggests a slightly higher moment of inertia with respect previous publications, indicating a lesser degree of differentiation. Key Points: Joint analysis of the Juno and Galileo data leads to a Ganymede's degree‐2 gravity compatible with hydrostatic equilibrium within 1− σ The data hints at regional gravity anomalies with amplitudes exceeding those inferred by Cassini for Titan Treatment of non‐hydrostatic effects leads to wider confidence intervals for the derived moment of inertia with respect to previous studies